2017
DOI: 10.2147/ndt.s119648
|View full text |Cite
|
Sign up to set email alerts
|

Visual–spatial training efficacy in children affected by migraine without aura: a multicenter study

Abstract: Routinely in the clinical practice, children affected by migraine without aura (MwA) tend to exhibit severe and persistent difficulties within cognitive processes such as attention, memory, and visual–motor integration (VMI) skills. The aim of this study was to assess the visual–spatial and visual–motor abilities among a sample of children with MwA and the effects of a specific computerized training. The study population was composed of 84 patients affected by MwA (39 girls and 45 boys; mean age: 8.91±2.46 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(37 reference statements)
1
4
1
Order By: Relevance
“…Moreover, we found no statistically significant difference between patients and controls in terms of visuo-motor skills; this is far different from what reported by Precenzano and co-workers ( 19 ), who, however, showed that this deficit could be remediated through a neuropsychologial rehabilitative intervention.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, we found no statistically significant difference between patients and controls in terms of visuo-motor skills; this is far different from what reported by Precenzano and co-workers ( 19 ), who, however, showed that this deficit could be remediated through a neuropsychologial rehabilitative intervention.…”
Section: Discussioncontrasting
confidence: 99%
“…Effectiveness of the Nintendo Wii Fit Plus™ system as a rehabilitative device in these patients was suggested ( 55 ). Also, Precenzano et al showed the efficacy of a specific software training (“Allenare le abilitsuo-spaziali”) for enhancing the visuospatial abilities ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cognitive training-only protocol was scheduled in a total of 20 one-hour individual sessions twice per week. The protocol was based on previous studies for cognitive impairment [8,[31][32][33][34][35][36] and for migraine [29]. The goal was to engage the three core executive functions: inhibition, working memory and shifting [55].…”
Section: Cognitive Training Only Protocolmentioning
confidence: 99%
“…Recent studies support the efficacy of non-pharmacological treatments in the management of migraine [12,22,23]. In the context of existing treatments for migraine, any treatments may act on sensitization pain modulation other on habituation: active exercise may result in neuroplasticity, through the release of the brain-derived neurotrophic factor, and in pain modulation, through the activation of endogenous systems [24][25][26][27][28]; cognitive training may result in neuroplasticity and global cognition, through the enhance of the performance on cognitive functions [29][30][31]. However, it seems that there are no treatments that may act both on sensitization and on habituation in people with migraine.…”
Section: Introductionmentioning
confidence: 99%